Maternal Dietary Protein Patterns in Pregnancy and Risk of Infant Eczema. (29th May 2020) - Zeng, Jingjing; Wu, Weijia; Chen, Yajun; Jing, Jin; Cai, Li
Abstract: Objectives: To study the relationship between maternal dietary protein patterns in pregnancy and the risk of infant eczema. Methods: A total of 714 mother-child pairs from a birth cohort in Guangzhou, China were studied. Maternal dietary intake was collected by a face-to-face food frequency questionnaire(FFQ) at 20–28 weeks' gestation, and protein intake of each food group was calculated for subsequent K-means cluster analysis to determine dietary protein patterns. Telephone interviews were used to collect parent-reported infant eczema data at age 6 months. The association between maternal dietary protein patterns and infant eczema was tested by using logistic regression models, after adjustment for potential confounders. Results: Cumulative incidence of eczema by 6 months of age was 51.26%. Four dietary protein patterns were identified according to the dietary protein sources, including poultry pattern (characterized by a relatively higher protein intake from poultry), plant pattern (characterized by a relatively higher protein intake from grain, soybean, vegetables, nuts and seeds), dairy and egg pattern (characterized by a relatively higher protein intake from dairy, eggs, and fruits), and red meat and seafood pattern (characterized by a relatively higher protein intake from red meat, fish and seafood). Compared to the poultry dietary pattern, plant pattern and dairy and egg pattern were associated with a reduced risk of developing infant eczema: the adjusted odds ratios (95% confidence interval) were 0.572(0.330–0.992) and 0.288(0.279–0.854) respectively. No such association was observed in red meat and seafood pattern. Conclusions: The maternal plant and dairy and egg dietary protein patterns in pregnancy may be preventive against infant eczema. Funding Sources: This work was supported by the National Natural Science Foundation of China (81, 602, 862) and the Sanming Project of Medicine in Shenzhen (SZSM201803061).